2019
DOI: 10.1186/s12967-019-2059-0
|View full text |Cite
|
Sign up to set email alerts
|

Red meat and dietary iron intakes are associated with some components of metabolic syndrome: Tehran Lipid and Glucose Study

Abstract: Background This study was conducted to investigate whether the daily consumption of haem, non-haem, total iron and red meat can affect the occurrence of metabolic syndrome (MetS) and its components. Methods Eligible adults (n = 4654) were selected from among participants of the Tehran Lipid and Glucose Study with an average follow-up of 3.8 years. Dietary intakes were assessed using a valid and reliable semi-quantitative food frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
2
27
1
Order By: Relevance
“…Dietary non-haem iron made up 91.4% of total iron intake in the present study, which is well in line with a typical Western diet [ 42 ]. We found that dietary haem iron intake was not associated with FPG in our study population, corroborating findings from large population-based studies in other disease settings [ 30 , 43 ]. By contrast, there was a significant inverse association between non-haem iron intake and FPG.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Dietary non-haem iron made up 91.4% of total iron intake in the present study, which is well in line with a typical Western diet [ 42 ]. We found that dietary haem iron intake was not associated with FPG in our study population, corroborating findings from large population-based studies in other disease settings [ 30 , 43 ]. By contrast, there was a significant inverse association between non-haem iron intake and FPG.…”
Section: Discussionsupporting
confidence: 91%
“…There has been no lack of studies on dietary iron intake and markers of glucose metabolism [ 2 , 3 , 28 , 29 , 30 , 31 ]. However, they have produced differing results and currently there is no consensus on whether or not habitual dietary iron intake affects blood glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The overall study characteristics are displayed in Table 2 [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Iran was the most represented country ( n = 55,592, 76.6%).…”
Section: Resultsmentioning
confidence: 99%
“…This finding may be partially attributed to the relatively lower intakes of red and processed meats and saturated fatty acids and higher intakes of legume and legume products in participants with higher CHEI scores. High intakes of red and processed meats and saturated fatty acids have been reported to be associated with increased prevalence of hypertriglyceridemia [ 45 , 46 ], and substitution legumes for red meats results in significant reduction in triglyceride concentrations in overweight type 2 diabetic patients [ 47 ]. Compared to DBI-16, CHEI scores were not associated with other lipid and lipoprotein profiles or glucose homeostasis biomarkers, indicating that CHEI may not be suitable for comprehensive evaluations of the relationships between diet quality and cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%